Savannah chimpanzee (Pan troglodytes verus) nesting behavior in the unprotected area of Tikankali near to a mining exploitation and the Niokolo Koba National Park in Senegal - Diallo, Dame; Ndiaye, Papa Ibnou; Badji, Landing; Pruetz, Jill D. (Frontiers in Ecology and Evolution, 2024)
This work focuses on the nesting behavior of the West African chimpanzee (Pan troglodytes verus) in the anthropized habitats of the village of Tikankali and its surroundings. Studies on chimpanzee nesting behavior are carried out at several sites of Senegal but never in Tikankaly.Thus, proximity with the Niokolo Koba National Park and the presence of a gold mining industry mean that data on chimpanzee nesting behavior and anthropogenic impacts in their habitats for decisions-making about chimpanzee conservation in this area. We recorded a total of 213 chimpanzee nests during two surveys over a distance of 47.81 km (i.e., 47.81 km x 2). Data were collected in October 2020 and October 2021. The majority of nests (63%) were found in wooded savannah, 19% in bamboo savannah, 09% in gallery forest and 07% in open forest.The results showed that 22 plant species belonging to 08 families are used for chimpanzee nests in and around Tikankali. However, half of the nests were in Pterocarpus erinaceus (53%); followed by Hexalobus monopetalus (8%); Diospyros mespiliformis (6%), Piliostigma thonningii (6%), Lannea acida (6%); and Grewia bicolor (4%). The average height of trees used as chimpanzee nest supports was 9.88 m (SD=3.60) and the average height of nests was 7.46 m (SD=3.23). Linear regression analysis (r=0.84; N=213; p< 0.05) suggested a preference for nesting at a particular height but also that nest height is a function of the supporting tree's height. The current study contributes to the knowledge of chimpanzee nesting behavior in Tikankali, the anthropogenic disruption and will help in the implementation of a good chimpanzee management and conservation strategy in Senegal.